(3JegjO GdeSJbQ dJMbjb eYfi GdeeQs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3GdehUd s)
(3ChdgG (B:s
(3GdeeQ ai GddZI eTJb ef GdEMJjGR jbY Ydi faS GdaYd hYdi GdecGf GdPi jhLO ajg ef GdaGYd , aQHeG Med Ydi GdeQhQ faSg , hQHeG Med Ydi ehVY GdeQhQ s
(3BNQgG (B:s
(3Ke dGjNdh GdCeQ ajgeG HYO Pdc ef GdfXQ HMSH CUhd UfGYI GdCMcGe , hde jhJ efgG NWC jYfi HGdEHGfI Yf Pdc Je GdcJGH hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B245(3C (B- (3U(B267(3Hs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI HgG CTcGd gfOSjI hLOGhds
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3GdfSNI ebGHdI Ydi CUd GdCUd ChQGbgG GdCNjQI eVWQHI GdJQJjH YfO GdJLdjO s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3Gdadcs